Salafism in Malaysia: historical account on its emergence and motivations - Malik, Maszlee (2015)
The term Salafism refers to an interpretation of Islam that seeks to restore Islamic faith and practice to the way they existed at the time of Prophet Muhammad and the early generations of his followers. Since this early period represented the golden age of Islam in its pure form, Salafis believe it should be the example followed by all Muslims today. Salafism as a trend and theological movement has been a point of interest to many researchers due to the current global political escalation. It has been a focal point of issues related to global terrorism, radicalism, post-Arab Spring politics, religious trends as well as theological debates. Salafism, more often known as Wahabism, has come to Malaysia at different times and with different motivations. The early brand of Salafism in pre-Malaysia Tanah Melayu, or Malaya, was the emergence of the early 20th century reformist Salafi movement, known as Kaum Muda, inspired by the Middle Eastern Abduh-Afghani Pan Islamism. Despite the differences between that and the current global Salafism they share the same roots. Additionally, according to numerous historical accounts, the current Salafi trend in Malaysia is closely related to the global Islamic revivalism of the 1970s and 1980s, and was also affected by the return of Malaysian students studying abroad during the 1990s and early 2000s. Evidence has shown that the emergence of Salafism in Malaysia has contributed directly and indirectly to the mainstream discourse of Islamic theology and Islamic worldview amongst Malaysian Muslims in general, and Islamic organizations in particular. This paper employs a descriptive approach in explaining the emergence of Salafism in Malaysia and offers a critical examination of certain historical events that led to the existence of the different trends and groupings of Salafism in Malaysia and its implications for Islamic discourse in the country.